2009
DOI: 10.4049/jimmunol.0804090
|View full text |Cite
|
Sign up to set email alerts
|

Novel Function of CRTH2 in Preventing Apoptosis of Human Th2 Cells through Activation of the Phosphatidylinositol 3-Kinase Pathway

Abstract: It is now well established that interaction of PGD2 with chemoattractant receptor- homologous molecule expressed on Th2 cells (CRTH2) promotes chemotaxis and proinflammatory cytokine production by Th2 lymphocytes. In this study we show a novel function of CRTH2 in mediating an inhibitory effect of PGD2 on the apoptosis of human Th2 cells induced by cytokine deprivation. This effect was mimicked by the selective CRTH2 agonist 13,14-dihydro-15-keto-PGD2, inhibited by the CRTH2 antagonists ramatroban and TM30089,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 61 publications
2
46
0
Order By: Relevance
“…In recent years, increasing evidence suggests that through its action on CRTH2, PGD 2 elicits many proinflammatory responses in leukocytes, including chemotaxis of eosinophils, basophils, and Th2 cells (10,11), cytokine production by Th2 cells (12,13), and proinflammatory protein expression by eosinophils and Th2 cells (12,14). Our recent studies also demonstrated that activation of CRTH2 suppresses Th2 cell apoptosis (15), a process that is likely to impede the resolution of allergic inflammation. Allergic responses mediated by IgE, mast cells, Th2 cells, and eosinophils are dramatically reduced in mice in which CRTH2 is genetically ablated or by small molecule CRTH2 antagonists (16)(17)(18)(19)).…”
mentioning
confidence: 87%
“…In recent years, increasing evidence suggests that through its action on CRTH2, PGD 2 elicits many proinflammatory responses in leukocytes, including chemotaxis of eosinophils, basophils, and Th2 cells (10,11), cytokine production by Th2 cells (12,13), and proinflammatory protein expression by eosinophils and Th2 cells (12,14). Our recent studies also demonstrated that activation of CRTH2 suppresses Th2 cell apoptosis (15), a process that is likely to impede the resolution of allergic inflammation. Allergic responses mediated by IgE, mast cells, Th2 cells, and eosinophils are dramatically reduced in mice in which CRTH2 is genetically ablated or by small molecule CRTH2 antagonists (16)(17)(18)(19)).…”
mentioning
confidence: 87%
“…Apoptosis of Th2 cells was measured after the withdrawal of IL-2 treatment as described previously (Xue et al, 2009). The cells were treated with PGD 2 (100 nM) in the presence and absence of various concentrations of OC000459 (1-1000 nM) for 16 h. Cells were then harvested and transferred to annexin-binding buffer, followed by incubation with phycoerythrin-annexin V/PI at room temperature for 15 min according to the manufacturer's (Invitrogen) instructions.…”
Section: Crth2mentioning
confidence: 99%
“…CRTH2 is coupled to Gi-type G proteins. Previous studies reported that CRTH2 agonism activates PI3K, which then suppresses IL-2-induced apoptosis in Th2 cells (39). Other groups showed that the constitutive activation of PI3K, by creating a deficiency in the PTEN gene, inhibits the expression of proinflammatory cytokines, including TNF-a and IL-6, in macrophages (40).…”
Section: Discussionmentioning
confidence: 99%